EVALUACIÓN DEL USO POTENCIAL DE LOS RESIDUOS EN EL PROCESO DE BIODIGESTIÓN ANAERÓBICA PARA LA PRODUCCIÓN DE BIOGÁS. - Gámez Ávila, Cindy Carolina
Research on the obtaining of renewable energies has been oriented to the search of new sources of raw material, that allow to obtain energy in a safe, efficient and economic way. According to the above, the objective of this work was to evaluate waste for anaerobic biodigestion processes in the production of biogas. Three substrates were physicochemically characterized as possible inputs in the digestion and co-digestion process: Substrate 1 porcine manure Substrate 2 kitchen waste and Substrate 3: Mixture of substrate 1 and substrate 2. The results obtained showed that the total solids for the manure are in the optimum range for Biodigestion processes (15% and 49%) with a value of 33.22%, kitchen waste could present a higher methane production and results of volatile solids, which are 91% , 96%, 75.89% and 70.35%, for the substrates of kitchen waste, manure and mixture respectively.